Antiviral COVID-19 protein and molecular docking: In silico characterization of various antiviral compounds extracted from Arisaema jacquemontii Blume - Shehzadi, Sara; Khan, Shujaul Mulk; Mustafa, Ghazala; Abdullah, Abdullah; Khan, Ilham; Ahmad, Zeeshan; Han, Heesup; Yu, Jongsik; Park, Junghyun; Raposo, António (Frontiers in Public Health, 2022)
Arisaema jacquemontii Blume is a highly medicinal and poisonous plant belonging to the family Araceae. It is used to treat several deadly diseases, including viral infections. It has antioxidant, anti-cancerous, antimalarial, anti-vermicidal and antiviral activity. Therefore, five parts of the Arisaema jacquemontii Blume plant i.e., leaf, seed, stem, pulp and rhizome extract, were evaluated for metabolic and in-silico characterization of probable compounds using Gas Chromatography Mass Spectrometry (GC-MS) analysis. A total of 22 compounds were isolated from the methanolic extracts of A. jacquemontii Blume. Selected antiviral COVID-19 protein Main protease (6LU7) was docked against the obtained compounds. Different affinities were obtained through various compounds. The best results were shown by three different compounds identified in the rhizome. These compounds reflected maximum binding affinity is – 8.1kJ/mole. Molecular docking (MD) findings indicate that these molecules have the highest binding energy and hydrogen bonding interactions. The binding mode of interaction was discovered to be reasonably effective to counteract against SARS virus COVID-19. The findings of this study could be extremely useful in the development of more phytochemical-based COVID-19 therapeutics.